2021
DOI: 10.1002/joc.7413
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of observed sea surface temperature variation by the quasi‐biweekly oscillation in the tropical western Pacific during boreal summer

Abstract: Using 17‐year in situ buoy observations, this study investigates how sea surface temperature (SST) over the tropical western Pacific Ocean is modulated by the quasi‐biweekly oscillation (QBWO) during boreal summer. The 10‐buoy mean phase‐by‐phase composites of SST indicate that SST evolution lags behind the convection cycle by approximately one quarter, with the maximum SST occurring in Phase −90° (29.68°C) and the minimum SST occurring in Phase 90° (29.37°C). The diurnal cycle of SST (dSST) is in phase with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
2
2
0
Order By: Relevance
“…The response in the sea surface turbulent heat fluxes to QBWO from Yang et al. (2021) is comparable to this study. Zhu et al.…”
Section: Summariessupporting
confidence: 86%
See 2 more Smart Citations
“…The response in the sea surface turbulent heat fluxes to QBWO from Yang et al. (2021) is comparable to this study. Zhu et al.…”
Section: Summariessupporting
confidence: 86%
“…The response in the sea surface turbulent heat fluxes to QBWO from Yang et al (2021) is comparable to this study. Zhu et al (2020) revealed a weaker R sd anomaly (60 W m −2 ) and a stronger Q l anomaly (−45 W m −2 ).…”
Section: Summariessupporting
confidence: 82%
See 1 more Smart Citation
“…The SST DV is a complex phenomenon influenced by various factors, such as solar radiation, sea surface winds, clouds, precipitation, dynamic ocean processes, and biological processes [9,33,34]. In particular, solar radiation is the primary driver of SST DV, causing the upper ocean to absorb a significant amount of heat, resulting in a positive correlation with SST DV.…”
Section: The Factors Influencing Sst DVmentioning
confidence: 99%